A new young galactic supernova remnant containing a compact object: G15.9+0.2 - Reynolds, Stephen P. (2006)
We identify the radio-emitting shell-type supernova remnant G15.9 0.2 as a relatively young remnant containing an X-ray point source that may be its associated neutron star. The integrated spectrum of the remnant shell obtained from our 30 ks exploratory Chandra observation shows very strong lines that require elevated element abundances from ejecta, in particular of sulfur. A plane-shock model fit gives a temperature (0.8, 1.0) keV, an ionization kT p 0.9 timescale cm3 s, and a sulfur abundance of 2.1 (1.7, 2.7) times solar (90% confidence 10 n t e p 6 (4, 9) # 10 limits). Two-component models with one solar and one enriched component are also plausible, but they are not well constrained by the data. Various estimates give a remnant age of order 103 yr, which would make G15.9 0.2 among the dozen or so youngest remnants in the Galaxy. The sparse point-source spectrum is consistent with either a steep power law or a keV blackbody. The spectrum is absorbed by a H column density G ∼ 4 kT ∼ 0.4 NH ∼ cm2 similar to that required for the remnant shell. The implied 2–9.5 keV source luminosity is about 22 4 # 10 1033 ergs s1 for an assumed distance of 8.5 kpc consistent with the high absorption column. We suggest that the point source is either a rotation-powered pulsar or a compact central object.